Response of environmental variables and microbial community to sodium percarbonate addition to contaminated sediment. (November 2018) - Pan, Hanping; Yang, Xunan; Zhong, Yuming; Xu, Meiying; Sun, Guoping
Abstract: Sodium percarbonate (SPC) is a common reagent used for in situ remediation of contaminated soil. Current studies focus on the effects of SPC on pollutant removal; however, a knowledge gap exists for the biochemical process following SPC addition. In this study, a microcosm batch experiment was conducted to investigate the residual effect caused by different doses of SPC addition on native microbial communities, as well as on the environmental variables of contaminated sediments. The obtained results showed that the more SPC was added, the more dissolved matters were generated and the oxidation-reduction potential was lowered. Furthermore, the metabolic activities of the microbial community were enhanced and the microbial community structure responded differently to different SPC doses: the microbes that increased at high SPC dose mainly belonged to the phylum Firmicutes, the class Clostridia, and the genera Petrimonas and Proteiniclasticum . The microbes that increased at medium SPC dose mainly belonged to the class Alphaproteobacteria and the genus Brevundimonas . In contrast, vulnerable microbes mainly belonged to the phylum Acidobacteria, the class Caldisericia, Holophagae, and the genus Sulfuricurvum . Microbes capable of fermentation, ureolysis, and chemohetrotrophy increased. These results indicate that SPC addition could indirectly provide both electron acceptors and donors, thus improving the metabolic activities of the microorganisms in the contaminated sediment. Furthermore, the utilized SPC dose should be considered to achieve the optimal benefit for in situ remediation. This study forms a valuable reference for the application of SPC in ecological engineering. Highlights: Increased SPC addition increased the generation of dissolved matters. SPC addition enhanced the metabolic activity of the native microorganisms. Different SPC doses influenced the microbial community structure differently. Microbes with fermentation, ureolysis, and chemohetrotrophy capabilities increased. These increased microbes strongly correlated to DOC, carbonate, and phosphate.